2022
DOI: 10.4314/gjpas.v28i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Malaria And Intestinal Parasitic Co-Infection Among Diabetic Patients In Calabar.

Abstract: Background: Malaria and intestinal parasitosis is a public health problem among diabetic patients, therefore, this work evaluates the prevalence of intestinal parasitic infection and malaria co-infections in diabetics. Materials and Methods Capillary blood and fecal samples were collected from 190 diabetic patients at the outpatient clinic of University of Calabar Teaching Hospital and Navy Reference Hospital Calabar and another batch of capillary blood and fecal samples from 110 non-diabetic subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In the present study, the overall prevalence of EPIs among diabetic patients was 82.67% while 17.33% was recorded among nondiabetic patients. Tis fnding is consistent with similar studies [12,22,[29][30][31] that reported higher infection of EPIs among patients with diabetes compared to nondiabetic patients. However, the study disagrees with an earlier study in Cameroon [32] which reported a higher prevalence among nondiabetic patients at 23.5% compared to diabetic patients at 10.0%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the overall prevalence of EPIs among diabetic patients was 82.67% while 17.33% was recorded among nondiabetic patients. Tis fnding is consistent with similar studies [12,22,[29][30][31] that reported higher infection of EPIs among patients with diabetes compared to nondiabetic patients. However, the study disagrees with an earlier study in Cameroon [32] which reported a higher prevalence among nondiabetic patients at 23.5% compared to diabetic patients at 10.0%.…”
Section: Discussionsupporting
confidence: 91%
“…Approximately, 30% of the world's population is at risk of enteric parasitic infections especially immunocompromised individuals and the incidence has rapidly increased in recent years [21]. Additionally, there has been a misconception that parasitic infections occur only in the tropical areas; however, it has also gained momentum in the temperate and subtropical regions, and hence it requires urgent attention and scrutiny for better health outcomes [22].…”
Section: Introductionmentioning
confidence: 99%